Correlation of Navicular Drop Height and Force Foot Distribution Characteristic and Pelvic Drop in Asymptomatic Runners - Tenriwulan, Andi Fadhilah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Objective: To explore the difference of performance between lower limbs and correlation of the navicular drop height and force distribution parameters during running. Material and Method: This study was conducted in the annual running performance test of Physical Therapy Center, Mahidol University. Before running test, navicular drop test was performed. Force distribution parameters were recorded over 7 minutes during running on the Force Distribution Measurement Treadmill (FDM-T) system. Contralateral pelvic drop (CPD) was captured with a video camera. Paired-samples t-test and Pearson or Spearman rank correlation tests were used for statistical analysis. Result: Twenty-nine participants were enrolled in this study. They were asymptomatic runners (novice and recreational). The finding showed that there was no correlation of navicular drop height and force distribution parameters and foot rotation. There were no significant differences of all parameters except with navicular drop height. There was significant difference of navicular drop height between legs in runners. For the pelvic obliquity, the result showed non-significant difference between non-dominant 95% CI (2.5 – 4.5) and dominant 95% CI (3 – 5) (p = 0.59) with low effect size (d = 0.2). Conclusion: In asymptomatic male and female runners, no significantly side-to-side difference during dynamic running test is an expectation for clinical observation. Typical range of CPD during running might be 3-5 degrees. Based on our finding, navicular drop may not a good predictor for force distribution characteristics during running test.